Asociacionismo juvenil - Rosa Mª Sandín Romano (Universidad de La Rioja, 2013)
This article shows the analysis and the first clonclusions about a sociologic investigation realizated in La Rioja, about the level of young associationism. This investigation has been greated by the youngs Advicer Institution from the Government of La Rioja. The conclusions obtained allow us to know more about the demand of young associationism and both the necessities to change the actually initiatives or to creaty new others.